PELUANG DAN STRATEGI PENJUALAN MELALUI INTERNET MARKETING - Munawaroh Munawaroh (Jurnal Ilmiah Econosains, 2011)
ABSTRACT The purpose of this journal is to mention of how the opportunity of internet marketing and the strategy of selling via internet marketing, The community of Indonesian now become the potential buyer because more than 30 million users of internet in Indonesia now. So that, this is the challenge for us to make the business based on e-commerce and application the strategy of selling via internet marketing.Keywords: opportunity, strategy, e-commerce, internet marketing,